A zinc selective oxytocin based biosensor. Issue 1 (29th November 2019) - Mervinetsky, Evgeniy; Alshanski, Israel; Tadi, Kiran Kumar; Dianat, Arezoo; Buchwald, Jörg; Gutierrez, Rafael; Cuniberti, Gianaurelio; Hurevich, Mattan; Yitzchaik, Shlomo
Abstract : A Zn 2+ selective biosensor was developed by anchoring oxytocin to the surface through acylation of the terminal amine, which blocks the competing Cu 2+ binding. Abstract : Oxytocin is a peptide hormone with high affinity to both Zn 2+ and Cu 2+ ions compared to other metal ions. This affinity makes oxytocin an attractive recognition layer for monitoring the levels of these essential ions in biofluids. Native oxytocin cannot differentiate between Cu 2+ and Zn 2+ ions and hence it is not useful for sensing Zn 2+ in the presence of Cu 2+ . We elucidated the effect of the terminal amine group of oxytocin on the affinity toward Cu 2+ using theoretical calculations. We designed a new Zn 2+ selective oxytocin-based biosensor that utilizes the terminal amine for surface anchoring, also preventing the response to Cu 2+ . The biosensor shows exceptional selectivity and very high sensitivity to Zn 2+ in impedimetric biosensing. This study shows for the first time an oxytocin derived sensor that can be used directly for sensing Zn 2+ in the presence of Cu 2+ .